Assessing mental health transition readiness in youth with medical conditions - Wendy N. Gray; Lauren Partain; Erin Benekos; Carlos Konishi; Adrianne Alpern; Michael Weiss (Health Care Transitions)
Purpose: Many youth with medical conditions also have co-occurring mental health concerns. Limited attention has been given to the mental health transition needs of these youth. We explore bringing transition readiness assessment into the mental health care of youth with co-occurring disorders. Design and Methods: Mental health transition readiness was assessed in transition-aged youth seen in a hospital-based specialty mental health clinic for youth with co-occurring medical and mental health conditions. Patients and/or parents reported on their awareness of transition policies and experiences. Clinicians formally assessed youth mental health transition readiness using the TRXANSITION Index. Results: Only 46.53 % of families knew about the clinic’s transition policy. Less than 1/3 reported their provider ever mentioning transition and only 6.93 % knew the deadline for transfer to adult care. Few patients had a transition goal in their treatment plan, even when required by the payor. By assessing transition readiness, clinicians were able to identify deficits in need of remediation in 95 % of patients. Transition readiness was highest in the following domains of the TRXANSITION Index: Ongoing support (85.15 %), Adherence (78.38 %), and Trade/School (71.29 %). Transition readiness was lowest in New Providers (30.94 %), Rx/Medications (37.99 %), and Insurance (42.57 %). Few knew when their current health insurance coverage would end (10.89 %) or how to get health insurance coverage when they became an adult (11.88 %). Mental health transition readiness and medical condition transition readiness did not differ in a sub-sample of youth with available data, t(14) = −1.33, p =.20. Conclusion: Mental health transition readiness is suboptimal in youth with co-occurring mental health and medical conditions. Findings point to specific targets for future intervention to improve patient mental health transition readiness and patient/family awareness of transition practices.